2014
DOI: 10.3892/mmr.2014.1981
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun transactivates Puma gene expression to promote osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disorder in which genetic, hormonal, mechanical and ageing factors affect its progression. Current studies are focusing on chondrocytes as a key mediator of OA at a cellular level. however, the mechanism underlying chondrocyte apoptosis remains unclear. PUMA is a pro-apoptotic member of the BH3-only subgroup of the Bcl-2 family and is involved in a large number of physiological and pathological processes. In the present study, we examined whether PUMA has a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…It has also been demonstrated that ASK1 activity is inhibited through its interaction with thioredoxin and that oxidation of (Cys 32 , Cys 35 thiol residues) of thioredoxin (Trx) in response to H 2 O 2 disrupts this interaction, thereby resulting in ASK1 activation [41]. In agreement with Lu and co-workers [42], our immunohistochemistry studies have revealed that Then after, cells were stained with Hoechst dye (a 0 -j 0 ) and anti-p53 (a 00 , b 00 ), anti-c-Jun (c 00 , d 00 ), anti-Bax (e 00 , f 00 ), anti-Caspase 3 (g 00 , h 00 ), and anti-DJ-1 (i 00 -j 00 ).…”
Section: Discussionmentioning
confidence: 56%
“…It has also been demonstrated that ASK1 activity is inhibited through its interaction with thioredoxin and that oxidation of (Cys 32 , Cys 35 thiol residues) of thioredoxin (Trx) in response to H 2 O 2 disrupts this interaction, thereby resulting in ASK1 activation [41]. In agreement with Lu and co-workers [42], our immunohistochemistry studies have revealed that Then after, cells were stained with Hoechst dye (a 0 -j 0 ) and anti-p53 (a 00 , b 00 ), anti-c-Jun (c 00 , d 00 ), anti-Bax (e 00 , f 00 ), anti-Caspase 3 (g 00 , h 00 ), and anti-DJ-1 (i 00 -j 00 ).…”
Section: Discussionmentioning
confidence: 56%
“…The control scrambled siRNA and siRNA for human p65 (sc-29410), and GSK3β (sc-35527) were from Santa Cruz Biotechnology. For stable transfection a shRNA-expressing plasmid that containing the p53-targeting sequence (CACCATCCACTACAACTACAT) [39], PUMA- targeting sequence (CCTGGAGGGTCATGTACAATCTC TT) [40], or a vector containing a scrambled sequence was transfected into HCT116 cells, followed transfection, cells were plated in 96-well plates in the presence of 5 μg/mL puromycin. The protein expression of puromycin-resistant clones was then analyzed by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The injury of articular cartilage induces changes in genes associated with cell signaling, response to injury, and wound healing(22). Recently, the pro-apoptotic gene, PUMA, has been shown to be activated by the c-Jun N-terminal kinase (JNK)/c-Jun pathway in the regulation of chondrocyte apoptosis in cartilage of patients with OA(23). Moreover, the Wnt signaling pathway, which is involved in both cartilage and bone tissue homeostasis(24), was found to be up-regulated while its inhibitor (FRZB) was down-regulated in cartilage from joints with moderate to severe OA damage(22).…”
Section: Genetic and Genomic Markersmentioning
confidence: 99%